Social development, social policy, and technocracy the Philippine experience - Dubsky, Roman (Philippine Journal of Public Administration, 1981)
The changing nature of development thought, particularly its social development/policy component, since 1960 is seen as highly influenced by the technocratic element, with social thought focusing on technocracy, Concern with social development was initially expressed through a framework of liberal values. Technocracy later became the dominant framework for social development policy. The peculiar technocratic element underlying the thought of social development is investigated. Dangers due to technocratic influence are identified. The Philippine experience in these matters has involved a position widely accepted by other developing states. This acceptance is primarily reflected in the tendency to treat social issues as part of the national planning process.